Binder, separator, secondary battery, and electric device
By combining high-temperature resistant PI polymer with inorganic nanoparticles and using independently designed polyurethane as a binder to form a porous separator, the existing separator's poor thermal stability and inorganic particles are solved, and efficient secondary battery circulation performance and safety are achieved.
Patent Information
- Application Number
- CN202411648979.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The existing microporous polyolefin separators have poor thermal stability and low porosity, which poses safety risks, and the coating of inorganic particles is prone to fall off during the battery circulation process, affecting the cycling performance of the battery.
A high-temperature resistant polyimide (PI) polymer substrate is used to combine with inorganic nanoparticles, and the polyurethane that is independently designed and synthesized as a binder is formed to form a porous separator. The degree of hydrogen bonding of the binder is between 40%±3% and 80%±3%, ensuring good adhesion between the separator and the inorganic particles.
The high temperature resistance of the separator and the stable circulation performance of the secondary battery are achieved, the problem of inorganic particles falling off is avoided, and the safety and working temperature range of the battery are significantly improved.
Smart Images

Figure BDA0005142557750000051 
Figure BDA0005142557750000061 
Figure BDA0005142557750000111
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the field of batteries, and in particular, to adhesives, separators, secondary batteries and electrical devices. Background Art
[0002] With the continuous advancement of information, materials and energy technology, lithium batteries have become a hot spot for research and application of new power technology in recent years due to their long cycle life, high energy density, and fast charging and discharging speed. The diaphragm in a lithium battery is located between the positive and negative electrodes. While avoiding direct contact between the two, it allows lithium ions to move quickly between the positive and negative electrodes to achieve charging and discharging. The performance of the diaphragm directly affects the cycle and safety performance of the battery. At present, conventional microporous polyolefin diaphragms are most widely used in lithium batteries due to their good chemical stability and high mechanical strength. However, their poor thermal stability and low porosity pose safety risks to the battery during charging and discharging. Therefore, the study of diaphragms with high temperature resistance and strong thermal stability is of great significance for greatly improving the operating temperature range and safety of lithium batteries.
[0003] As a high-performance polymer, polyimide (PI) has attracted more and more attention due to its outstanding advantages such as excellent thermal stability, high chemical stability and ability to withstand harsh working conditions. Therefore, the use of PI can be a means to improve the safety of LIB (lithium-ion battery). In addition, coating inorganic particles on the surface of the diaphragm is also an important means to improve the thermal stability of polyolefin diaphragms. Therefore, the PI diaphragm can be combined with inorganic particles to significantly improve the thermal stability of the porous diaphragm. However, it is difficult for traditional PI to adopt the same preparation method as polyolefin diaphragms, and the coated inorganic particles may fall off during the battery cycle and affect the battery cycle. Therefore, it is necessary to use a suitable method to develop a porous PI diaphragm coated with inorganic nanoparticles that is resistant to high temperature and lithium dendrites.
[0004] In summary, the existing microporous polyolefin separators have the following disadvantages:
[0005] Conventional microporous polyolefin separators have poor thermal stability and low porosity, which poses a safety hazard during battery charging and discharging. Polyolefin separators coated with inorganic particles have increased thermal stability, but there is a problem of inorganic particles falling off during battery cycling, affecting battery cycling. Summary of the invention
[0006] The present application combines a high temperature resistant PI polymer substrate with inorganic particles to obtain a porous separator with strong thermal stability and excellent cycle performance for secondary batteries.
[0007] Embodiments of the present application relate to a binder, including a polyurethane made of a polymer, an isocyanate and a chain extender, wherein the degree of hydrogen bonding of the polyurethane is between 40% ± 3% and 80% ± 3%, and optionally between 50% ± 3% and 70% ± 3%, and is optimal at about 70%. In the present application, the degree of hydrogen bonding of the polyurethane is regulated by regulating the structure of the polymer, isocyanate and chain extender. In some embodiments, the molar ratio of the polymer, isocyanate and chain extender is preferably 1:2:1. In some embodiments, the polymer includes polyethylene glycol, and the molecular weight of the polymer is between 500g / mol-2000g / mol. In some embodiments, the isocyanate includes one or both of isophorone diisocyanate and toluene-2,4-diisocyanate, and the chain extender includes one or both of adipic acid dihydrazide and hexamethylenediamine. In the present application, by regulating the degree of hydrogen bonding of the polyurethane, the diaphragm has better adhesion to the inorganic particles, and the cycle performance of the secondary battery formed thereafter is better.
[0008] Other embodiments of the present application provide a diaphragm, comprising: a polyimide (PI) polymer substrate having a porous structure; and an inorganic nanoparticle coating, comprising a binder and inorganic nanoparticles, wherein the binder comprises the above-mentioned binder. In the present application, a PI porous polymer substrate is used, and the inorganic nanoparticle coating adopts a polyurethane independently designed and synthesized as a binder, and the two are combined to achieve high temperature resistance of the diaphragm and stable circulation of the secondary battery. In some embodiments, the inorganic nanoparticle coating is disposed on both sides of the polyimide (PI) polymer substrate. In some embodiments, the inorganic nanoparticles include any one of ceramic particles and inorganic oxide solid electrolytes, and the inorganic oxide solid electrolyte includes one or more of lithium aluminum titanium phosphate, lithium lutetium yttrium titanate, lithium lanthanum zirconium tantalum oxide, and lithium lanthanum zirconium oxide.
[0009] The ceramic particles may include but are not limited to at least one of Al2O3 (including α, β, and γ types), SiO2, BaSO4, BaO, titanium dioxide (TiO2, rutile or anatase), CuO, MgO, Mg(OH)2, LiAlO2, ZrO2, carbon nanotubes (CNTs), BN, SiC, Si3N4, WC, BC, AlN, Fe2O3, BaTiO3, MoS2, α–V2O5, PbTiO3, TiB2, CaSiO3, molecular sieves (ZSM-5), clay, boehmite and kaolin, preferably Al2O3.
[0010] In some embodiments, the thickness of the inorganic nanoparticle coating is in the range of 0.5 μm-5 μm. This is because when the inorganic nanoparticle coating is too thick (e.g., >5 μm), it will affect the capacity of the secondary battery, and when the inorganic nanoparticle coating is too thin (e.g., <0.5 μm), it will affect the long-term cycle stability of the secondary battery.
[0011] In some embodiments, the mass ratio of the binder to the inorganic nanoparticles is in the range of 95: 5-99.8: 0.2, and further, 99: 1. In some embodiments, the inorganic nanoparticles include ceramic particles, inorganic oxide solid electrolytes, and the inorganic oxide solid electrolytes include one or more of lithium aluminum titanium phosphate, lithium lutetium yttrium titanate, lithium lanthanum zirconium tantalum oxide, and lithium lanthanum zirconium oxide.
[0012] The embodiments of the present application also provide a secondary battery including the above-mentioned separator.
[0013] Still other embodiments of the present application provide an electrical device including the secondary battery.
[0014] The present application uses a PI porous diaphragm substrate and an inorganic nanoparticle coating using independently designed and synthesized polyurethane as a binder. The combination of the two achieves high temperature resistance of the diaphragm and stable circulation of the secondary battery. DETAILED DESCRIPTION
[0015] This application uses PI as the polymer substrate. Compared with traditional PE / PP membranes, the thermal stability of the membrane made of PI polymer substrate is enhanced.
[0016] In addition, the inorganic nanoparticle coating in the diaphragm uses independently synthesized polyurethane as a binder, so that the binder can not only form a good hydrogen bond interaction with the PI polymer substrate, but also adhere the inorganic particles to the surface well, thereby achieving a perfect combination of the inorganic particles and the PI polymer substrate, and will not fall off during the cycle, thereby achieving an excellent cycle of the secondary battery.
[0017] An embodiment of the present application relates to a binder, comprising a polyurethane made of a polymer, an isocyanate and a chain extender, wherein the degree of hydrogen bonding of the polyurethane is between 40% ± 3% and 80% ± 3%, and optionally between 50% ± 3% and 70% ± 3%, and is optimal at about 70%. In the present application, the degree of hydrogen bonding of the polyurethane is regulated by regulating the structure of the polymer, isocyanate and chain extender. In some embodiments, the molar ratio of the polymer, isocyanate and chain extender is preferably 1:2:1. In some embodiments, the polymer includes polyethylene glycol, and the molecular weight of the polymer is between 500g / mol-2000g / mol. In some embodiments, the isocyanate includes one or both of isophorone diisocyanate and toluene-2,4-diisocyanate, and the chain extender includes one or both of adipic acid dihydrazide and hexamethylenediamine. In the present application, by regulating the degree of hydrogen bonding of the polyurethane, the diaphragm has better adhesion to the inorganic particles, and the cycle performance of the secondary battery formed thereafter is better.
[0018] Other embodiments of the present application provide a diaphragm, comprising: a polyimide (PI) polymer substrate having a porous structure; and an inorganic nanoparticle coating, comprising a binder and inorganic nanoparticles, wherein the binder comprises the above-mentioned binder. In the present application, a PI porous polymer substrate is used, and the inorganic nanoparticle coating adopts a polyurethane independently designed and synthesized as a binder, and the two are combined to achieve high temperature resistance of the diaphragm and stable circulation of the secondary battery. In some embodiments, the inorganic nanoparticle coating is disposed on both sides of the polyimide (PI) polymer substrate. In some embodiments, the inorganic nanoparticles include ceramic particles and inorganic oxide solid electrolytes, and the inorganic oxide solid electrolytes include one or more of lithium aluminum titanium phosphate, lithium lutetium yttrium titanate, lithium lanthanum zirconium tantalum oxide, and lithium lanthanum zirconium oxide.
[0019] In some embodiments, the thickness of the inorganic nanoparticle coating is in the range of 0.5 μm-5 μm. This is because when the inorganic nanoparticle coating is too thick (e.g., >5 μm), it will affect the capacity of the secondary battery, and when the inorganic nanoparticle coating is too thin (e.g., <0.5 μm), it will affect the long-term cycle stability of the secondary battery.
[0020] In some embodiments, the mass ratio of the binder to the inorganic nanoparticles is in the range of 95:5-99.8:0.2, and further, 99:1. In some embodiments, the inorganic nanoparticles include ceramic particles, inorganic oxide solid electrolytes, and the inorganic oxide solid electrolytes include one or more of lithium aluminum titanium phosphate, lithium lutetium yttrium titanate, lithium lanthanum zirconium tantalum oxide, and lithium lanthanum zirconium oxide. In the present application, when the mass ratio of the binder to the inorganic nanoparticles is controlled in the range of 95:5-99.8:0.2, the adhesion between the diaphragm and the inorganic particles and the excellent performance of the battery can be effectively guaranteed, and the optimum is reached when the mass ratio is 99:1.
[0021] Some embodiments of the present application provide a secondary battery, comprising: a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the separator comprises the above-mentioned separator.
[0022] The formation process of the secondary battery is described below.
[0023] (1) Preparation process of binder
[0024] Polyurethane is formed by using polymer, isocyanate and chain extender as raw materials, wherein the molar ratio of polymer, isocyanate and chain extender is preferably 1:2:1. In some embodiments, the polymer includes polyethylene glycol, and the molecular weight of the polymer is between 500g / mol and 2000g / mol. In some embodiments, the isocyanate includes one or both of isophorone diisocyanate and toluene-2,4-diisocyanate, and the chain extender includes one or both of adipic acid dihydrazide and hexamethylenediamine. In the present application, the degree of hydrogen bonding of the polyurethane is between 40%±3% and 80%±3%, and is optimal at around 70%.
[0025] Specifically, the synthesis of the polyurethane binder is described in detail by taking polyethylene glycol (PEG), isophorone diisocyanate and adipic acid dihydrazide as examples. The molar ratio of polyethylene glycol (PEG), isophorone diisocyanate and adipic acid dihydrazide is 1:2:1. Specifically, 2.5 g of polyethylene glycol (PEG) (molecular weight (Mn) is 500 g / mol) is charged into a three-necked round-bottom flask (capacity is suitable, such as 100 mL) equipped with a mechanical stirrer, and then heated and stirred at 110 ° C under vacuum for 30 minutes to remove moisture from the system. After the reaction system is cooled to 80 ° C, a mixture of isophorone diisocyanate (2.22 g) and dibutyltin dilaurate (0.02 g) dissolved in 5 mL of N, N-dimethylacetamide (DMAC) is quickly added to the PEG system; the reaction system is stirred for 3 h under N2 atmosphere and then cooled to 60 ° C. 0.87g of adipic acid dihydrazide was used as a chain extender and dissolved in 60mL DMAC at 100°C. The solution was then added to the reaction system and further reacted for 15h under stirring and N2 atmosphere. Finally, a viscous transparent solution of the polymer was obtained, and the obtained polymer solution was finally poured into a culture dish (a culture dish commonly used in the art), heated on a heating plate at 80°C overnight, and then vacuum dried at 80°C for 48h to obtain a polyurethane adhesive. The degree of hydrogen bonding can be obtained by Fourier infrared testing. The degree of hydrogen bonding of the polyurethane adhesive is 80%±3%.
[0026] The preparation methods of other polymers, isocyanates and chain extenders are similar to the methods discussed above, and the degree of hydrogen bonding of polyurethane can be regulated by regulating the structures of polymers, isocyanates and chain extenders. The degree of hydrogen bonding corresponding to the specific structures is shown in Table 1 below. Of course, the degree of hydrogen bonding of each type also fluctuates within a certain range and is not a fixed value.
[0027] Table 1 shows the degree of hydrogen bonding of polyurethane binders prepared with different polymers, isocyanates and chain extenders.
[0028]
[0029]
[0030] (2) Preparation process of diaphragm
[0031] Preparation of PI polymer substrate: Traditional membrane preparation methods or electrospinning methods can be used, that is, any method that can produce a porous membrane can be used. Taking the electrospinning method as an example, first prepare a PI solution (the mass fraction of the solution is between 0.5wt% and 20wt%, preferably 5wt%), and then use an electrospinning instrument to electrospin a 9-micron thick porous PI polymer substrate (or directly purchase an electrospun PI membrane).
[0032] Inorganic nanoparticle coating: Inorganic oxide nanoparticles are coated on the surface of the PI polymer substrate. The inorganic nanoparticles may include but are not limited to ceramic particles, inorganic oxide solid electrolytes, and the inorganic oxide solid electrolytes include but are not limited to lithium aluminum titanium phosphate (LATP), lithium lutetium yttrium titanate (LLTO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium lanthanum zirconium oxide (LLZO), etc. Here, the synthesis method of LATP is taken as an example, and other methods are similar.
[0033] LATP and the above-mentioned polyurethane binder are dissolved in a tetrahydrofuran solution according to a certain mass ratio, the concentration of the LATP solution is 3wt%, and the mass ratio of LATP to the binder ranges from 95:5 to 99.8:0.2, and can be optionally 99:1.
[0034] Preparation of the separator: The above LATP solution was coated on both sides of the PI polymer substrate and then dried. The thickness of the single layer coating was 0.5-5 μm, and the thickness of the single layer was optionally 2 μm. The total thickness of the separator was 13 μm.
[0035] The present application also provides a secondary battery and a corresponding electrical device, wherein the secondary battery includes the above-mentioned diaphragm, a positive electrode plate, a negative electrode plate, etc.
[0036] Preparation method of positive electrode sheet: dispersing positive electrode active material, positive electrode conductive agent and positive electrode binder in a solvent to form a uniform positive electrode slurry, coating the positive electrode slurry on the surface of positive electrode current collector, and forming a positive electrode active material layer on the positive electrode current collector after drying, cold pressing and other processes to obtain a positive electrode sheet. The ratio between the components in the positive electrode slurry can be set with reference to the conventional ratio, and is not limited here. Among them, the positive electrode active material is the positive electrode active material coated on the positive electrode current collector as commonly understood in the art. The type of positive electrode active material can be one or more of lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt manganese oxide (NCM) or lithium nickel cobalt aluminum oxide (NCA). The positive electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more mixed in any proportion. The positive electrode binder is selected from PVDF and one of its derivatives.
[0037] Preparation method of negative electrode sheet: Disperse negative electrode active material, negative electrode conductive agent and binder in solvent to form uniform negative electrode slurry, apply negative electrode slurry on the surface of negative electrode current collector, form negative electrode active material layer on negative electrode current collector after drying, cold pressing and other processes, and obtain negative electrode sheet. The ratio between the components in the negative electrode slurry can be set with reference to the conventional ratio, and is not limited here. In some embodiments, the negative electrode active material is the negative electrode active material on the negative electrode current collector as conventionally understood in the art. The type of negative electrode active material can be graphite material, silicon material, lithium metal or "composite material of graphite and silicon material". The negative electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotube, carbon nanofiber, etc. or a combination of two or more in any proportion. The negative electrode binder is selected from one of sodium carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyacrylic acid, lithium polyacrylate, fluororubber, PVDF or a combination thereof.
[0038] The electrolyte may be any electrolyte used in common liquid secondary batteries, such as sulfide electrolytes and halide electrolytes commonly found on the market.
[0039] Secondary battery
[0040] The positive electrode sheet, negative electrode sheet, electrolyte and separator described above are assembled into a secondary battery by a method commonly used in the art, wherein the positive electrode sheet, separator, negative electrode sheet, etc. are wound or stacked in sequence into a bare battery cell, and then packaged in, for example, an aluminum-plastic film, and an electrolyte is injected. After formation, packaging and testing, the assembled secondary battery is subjected to a cycle performance test. The secondary batteries prepared in this application are all lithium-ion secondary batteries.
[0041] Those skilled in the art will understand that the method for preparing the secondary battery described above is only an embodiment. Without departing from the contents disclosed in the present application, other methods commonly used in the art may be adopted. It should be noted that the battery prepared in the present application may also be a sodium ion secondary battery or a potassium ion secondary battery.
[0042] Those skilled in the art will understand that the above-described method for preparing the battery is only an example, and other methods commonly used in the art may be used without departing from the contents disclosed in the present application.
[0043] The reagents and raw materials used in the present invention are commercially available.
[0044] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.
[0045] Example 1
[0046] (1) Preparation of diaphragm
[0047] The preparation of the first binder is as described above: 2.5 g of polyethylene glycol (PEG) (molecular weight (Mn) of 500 g / mol) is placed in a three-necked round-bottom flask (capacity is suitable, such as 100 mL) equipped with a mechanical stirrer, and then heated and stirred at 110 ° C under vacuum for 30 minutes to remove moisture from the system. After the reaction system is cooled to 80 ° C, a mixture of isophorone diisocyanate (2.22 g) and dibutyltin dilaurate (0.02 g) dissolved in 5 mL of N, N-dimethylacetamide (DMAC) is quickly added to the PEG system; the reaction system is stirred for 3 h under N2 atmosphere and then cooled to 60 ° C. 0.87 g of adipic acid dihydrazide is used as a chain extender and dissolved in 60 mL of DMAC at 100 ° C. The solution is then added to the reaction system and further reacted for 15 h under stirring and N2 atmosphere. Finally, a viscous transparent solution of the polymer is obtained, and the obtained polymer solution is finally poured into a culture dish (a culture dish commonly used in the art), heated on a heating plate at 80° C. overnight, and then vacuum dried at 80° C. for 48 hours to obtain a polyurethane adhesive. The degree of hydrogen bonding can be obtained by Fourier infrared testing. The degree of hydrogen bonding of the polyurethane adhesive is 80%±3%.
[0048] Preparation of the diaphragm: First, prepare the PI solution (the mass fraction of the solution is 5wt%), and then electrospin a 9-micron-thick porous PI polymer substrate through an electrospinning instrument. After that, the inorganic nanoparticles LATP and the above-mentioned polyurethane binder are dissolved in a tetrahydrofuran solution at a mass ratio of 99:1, and the concentration of the LATP solution is 3wt%. Finally, the above-mentioned LATP solution is coated on both sides of the PI polymer substrate and then dried. The thickness of the single layer coating is 2μm, and the total thickness of the diaphragm is 13μm.
[0049] (2) Preparation method of positive electrode sheet (using nickel cobalt lithium manganese oxide positive electrode sheet for illustration):
[0050] Lithium nickel cobalt manganese oxide as a positive electrode active material, polyvinylidene fluoride as a binder, and Super P as a conductive agent are mixed in a weight ratio of 98:1:1, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on a current collector such as aluminum foil, and the aluminum foil is dried at room temperature and then transferred to an oven for drying.
[0051] (3) Preparation of negative electrode sheet (taking graphite as an example):
[0052] 30% silica + graphite (mass ratio of 3:7) as negative electrode active material, Super P as conductive agent, sodium carboxymethyl cellulose (CMC-Na) as thickener, styrene-butadiene rubber (SBR) as binder are mixed in a mass ratio of 96:1:1:2, deionized water is added, and negative electrode slurry is obtained under the action of a vacuum mixer; the negative electrode slurry is evenly coated on a current collector such as copper foil that has been coated with a single side of a positive electrode active material; the copper foil is dried at room temperature and then transferred to an oven for drying to obtain a negative electrode sheet.
[0053] (4) Electrolyte
[0054] It can be made of electrolytes commonly found in liquid secondary batteries, such as Li6PS5Cl.
[0055] (5) Secondary battery
[0056] The positive electrode sheet, negative electrode sheet, electrolyte and separator described above are assembled into a secondary battery by conventional methods in the art, wherein the positive electrode sheet, separator, negative electrode sheet, etc. are wound or stacked in sequence into a bare battery cell, and then encapsulated in, for example, an aluminum-plastic film, and the electrolyte is injected. After formation, packaging and testing, the assembled secondary battery is subjected to a cycle performance test.
[0057] Example 2
[0058] The preparation method is consistent with that of Example 1, except that the binder in Example 2 uses the second binder in Table 1 above.
[0059] Example 3
[0060] The preparation method is consistent with that of Example 1, except that the binder in Example 3 uses the third binder in Table 1 above.
[0061] Example 4
[0062] The preparation method is consistent with that of Example 1, except that the binder in Example 4 uses the fourth binder in Table 1 above.
[0063] Example 5
[0064] The preparation method is consistent with that of Example 1, except that the binder in Example 4 uses the fifth binder in Table 1 above.
[0065] Example 6
[0066] The preparation method is consistent with that of Example 1, except that the binder in Example 6 uses the second binder in Table 1 above, and the mass ratio of the inorganic nanoparticles LATP to the binder is 95:5.
[0067] Example 7
[0068] The preparation method is consistent with that of Example 1, except that the binder in Example 7 uses the second binder in Table 1 above, and the mass ratio of the inorganic nanoparticles LATP to the binder is 99.8:0.2.
[0069] Example 8
[0070] The preparation method is consistent with that of Example 1, except that the binder in Example 8 uses the second binder in Table 1 above, and the mass ratio of the inorganic nanoparticles LATP to the binder is 90:10.
[0071] Example 9
[0072] The preparation method is consistent with that of Example 1, except that the binder in Example 9 uses the second binder in Table 1 above, and the mass ratio of the inorganic nanoparticles LATP to the binder is 99.9:0.1.
[0073] Example 10
[0074] The preparation method is consistent with that of Example 1, except that the binder in Example 10 uses the second binder in Table 1, and the thickness of the single-layer coating of the separator is 0.5 μm.
[0075] Embodiment 11
[0076] The preparation method is consistent with that of Example 1, except that the binder in Example 11 uses the second binder in Table 1, and the thickness of the single-layer coating of the separator is 5 μm.
[0077] Example 12
[0078] The preparation method is consistent with that of Example 1, except that the binder in Example 12 uses the second binder in Table 1 above, and the thickness of the single-layer coating of the separator is 0.1 μm.
[0079] Example 13
[0080] The preparation method is consistent with that of Example 1, except that the binder in Example 13 uses the second binder in Table 1 above, and the thickness of the single-layer coating of the separator is 10 μm.
[0081] Embodiment 14
[0082] The preparation method is consistent with that of Example 1, except that the binder in Example 10 uses the second binder in Table 1, and the inorganic nanoparticles use LLTO.
[0083] Embodiment 15
[0084] The preparation method is consistent with that of Example 1, except that the binder in Example 11 uses the second binder in Table 1, and the inorganic nanoparticles use LLZTO.
[0085] Example 16
[0086] The preparation method is consistent with that of Example 1, except that the binder in Example 12 uses the second binder in Table 1 above, and the inorganic nanoparticles use LLZO.
[0087] Embodiment 17
[0088] The preparation method is consistent with that of Example 1, except that the binder in Example 13 uses the second binder in Table 1, and the inorganic nanoparticles are aluminum oxide.
[0089] Comparative Example 1
[0090] The preparation method is consistent with that of Example 1, except that the binder in Comparative Example 1 uses the second binder in Table 1 above, and the first binder is replaced by PVDF (polyvinylidene fluoride).
[0091] Performance Testing Methods
[0092] Cyclic capacity retention test: The secondary batteries in Examples 1-17 and Comparative Example 1 were cycled at 25°C in a 2.5-4.3V charge-discharge regime. After 1000 cycles, the discharge capacity of the battery at this time was divided by the discharge capacity of the first cycle, which is the capacity retention rate of the battery at a charge-discharge rate of 1C / 1C.
[0093] It should be noted that in this application, the secondary battery performance in Examples 1-17 and Comparative Example 1 is based on the battery assembled with 30% silicon oxide + graphite as the negative electrode and the nine-series positive electrode of lithium nickel cobalt manganese oxide. At the same time, the battery meets the requirements of more than 300 cycles at room temperature at 80% SOH and a 1C capacity of more than 170 mAh / g.
[0094] The test results are shown in Table 2 below.
[0095] Table 2. Secondary battery performance test results of Examples 1-17 and Comparative Example 1
[0096]
[0097]
[0098] From the comparison between Examples 1-17 and Comparative Example 1 in Table 2 above, it can be seen that the binder provided by the present application includes a polyurethane made of a polymer, an isocyanate and a chain extender, and when the degree of hydrogen bonding of the polyurethane is between 40% ± 3% and 80% ± 3%, the adhesion between the diaphragm and the inorganic particles is good, and the cycle performance of the secondary battery is good, and the number of cycles and the capacity of the secondary battery with a hydrogen bonding degree of 70% ± 3% shown in Example 2 are both optimal. The PVDF used in Comparative Example 1 has a very low degree of hydrogen bonding (almost none), poor adhesion to the diaphragm and inorganic particles, and the least number of cycles, which results in poor performance of the secondary battery.
[0099] In addition, by comparing Example 1 with Examples 2-4, it can be seen that the polyurethane in Example 1 has a high degree of hydrogen bonding (80% ± 3%), and the cohesive force is relatively large, which will make it harder, and the adhesion to the diaphragm and inorganic particles is limited, so that its number of cycles is less than the number of cycles of the secondary battery formed by the polyurethane of the binder in Examples 2-4 with a hydrogen bonding degree of 50% ± 3% to 70% ± 3%. Similarly, by comparing Example 5 with Examples 2-4, it can be seen that the polyurethane in Example 5 has a low degree of hydrogen bonding (40% ± 3%), and the adhesion to the diaphragm and inorganic particles is limited, so that its number of cycles is less than the number of cycles of the secondary battery formed by the polyurethane of the binder in Examples 2-4 with a hydrogen bonding degree of 50% ± 3% to 70% ± 3%. Comparing Example 3-4 with Example 2 (hydrogen bonding degree 70%±3%), it can be seen that the hydrogen bonding degree in Example 3-4 (hydrogen bonding degree 50%±3% and 60%±3%) is slightly lower, and the number of cycles and capacity of the secondary battery are worse than those in Example 2, and the improvement effect is limited.
[0100] Comparing Examples 2, 6-7 with Examples 8-9, it can be seen that the mass ratio of the binder and the inorganic nanoparticles is within the range of 95:5-99.8:0.2, which can better balance the number of cycles and battery capacity of the secondary battery, and can effectively ensure the adhesion between the diaphragm and the inorganic particles and the excellent performance of the battery, and when the mass ratio of the binder and the inorganic nanoparticles is 99:1 in Example 2, the effect is optimal. In Example 6, the mass ratio of the binder and the inorganic nanoparticles is 95:5, at which time the binder is relatively large, and the number of cycles of the secondary battery is longer. In Example 7, the mass ratio of the binder and the inorganic nanoparticles is 99.8:0.2, at which time the inorganic nanoparticles LATP is more, and the secondary battery capacity is higher. Comparing Example 8 with Examples 2, 6-7, it can be seen that when there is too much binder (the mass ratio of the binder and the inorganic nanoparticles is 90:10), the capacity of the secondary battery will be affected, thereby affecting the performance of the corresponding secondary battery, so that its improvement effect is limited. Comparing Example 9 with Examples 2 and 6-7, it can be seen that when the binder is too little (the mass ratio of the binder to the inorganic nanoparticles is 99.9:0.1), the long-term cycle stability of the secondary battery will be affected, thereby affecting the performance of the corresponding secondary battery, making its improvement effect limited.
[0101] Comparing Examples 10-11 and 12-13, it can be seen that the thickness of the inorganic nanoparticle coating is within the range of 0.5 μm-5 μm, thereby ensuring the cycle and capacity of the secondary battery. This is because when the thickness of the inorganic nanoparticle coating is small (e.g., 0.5 μm), the capacity of the secondary battery is high, and when the thickness of the inorganic nanoparticle coating is large (e.g., 5 μm), the number of cycles of the secondary battery is high. Therefore, the thickness of the inorganic nanoparticle coating is within the range of 0.5 μm-5 μm, which can balance the cycle and capacity of the secondary battery, and the thickness of the inorganic nanoparticle coating is optimal at 2 μm. When the inorganic nanoparticle coating in Example 12 is too thick (e.g., >5 μm), it will affect the capacity of the secondary battery, thereby limiting the improvement effect of the performance of the secondary battery, and when the inorganic nanoparticle coating in Example 13 is too thin (e.g., <0.5 μm), it will affect the long-term cycle stability of the secondary battery, thereby affecting the performance of the secondary battery, limiting its improvement effect.
[0102] It can be seen from Examples 14-17 that when the inorganic nanoparticles include aluminum oxide and inorganic oxide solid electrolytes, and the inorganic oxide solid electrolyte includes one or more of lithium aluminum titanium phosphate (LATP), lithium lutetium yttrium titanate (LLTO), lithium lanthanum zirconium tantalum oxide (LLZTO), and lithium lanthanum zirconium oxide (LLZO), the secondary battery of the present application has good cycle performance and capacity.
[0103] The features of several embodiments are summarized above so that those skilled in the art can better understand aspects of the present invention. Those skilled in the art should understand that they can easily use the present invention as a basis to design or modify other processes and structures for implementing the same purpose and / or achieving the same advantages as the embodiments introduced herein. Those skilled in the art should also appreciate that this equivalent construction does not deviate from the spirit and scope of the present invention, and that they can make multiple changes, substitutions and changes herein without departing from the spirit and scope of the present invention.
Claims
1. A binder, characterized in that: comprising a polyurethane made from at least a polymer, an isocyanate and a chain extender, The degree of hydrogen bonding of the polyurethane is between 40%±3% and 80%±3%.
2. The adhesive according to claim 1, characterized in that The degree of hydrogen bonding of the polyurethane is between 50%±3% and 70%±3%.
3. The adhesive according to claim 1, characterized in that The polymer includes polyethylene glycol, and the molecular weight of the polymer is between 500 g / mol and 2000 g / mol; the isocyanate includes one or both of isophorone diisocyanate and toluene-2,4-diisocyanate; and the chain extender includes one or both of adipic acid dihydrazide and hexamethylenediamine.
4. The adhesive according to claim 1, characterized in that The molar ratio of the polymer, the isocyanate and the chain extender is 1:2:
1.
5. A diaphragm, characterized in that: include: a polyimide polymer substrate having a porous structure; and an inorganic nanoparticle coating, disposed on at least one side of the polyimide polymer substrate, comprising a binder and inorganic nanoparticles, Wherein, the binder comprises the binder according to any one of claims 1-4.
6. The diaphragm according to claim 5, characterized in that The thickness of the inorganic nanoparticle coating is in the range of 0.5 μm to 5 μm.
7. The diaphragm according to claim 5, characterized in that The mass ratio of the binder to the inorganic nanoparticles is in the range of 95:5-99.8:0.
2.
8. The diaphragm according to claim 5, characterized in that The inorganic nanoparticles include at least any one of ceramic particles and inorganic oxide solid electrolytes, and the inorganic oxide solid electrolyte includes one or more of lithium aluminum titanium phosphate, lithium lutetium yttrium titanate, lithium lanthanum zirconium tantalum oxide, and lithium lanthanum zirconium oxide.
9. A secondary battery, characterized in that: include: A positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the separator comprises the separator according to any one of claims 5-8.
10. An electrical device, characterized in that: A secondary battery according to claim 9 is included.